REKAYASA PERANGKAT LUNAK KRIPTOGRAFI MENGGUNAKAN ALGORITMA RSA PADA SISTEM KEAMANAN FILE BERBASIS JAVA - Busran; Novernus Ayundha Putra (ITP Press, 2014)
Data security is a top priority on a data storage device, using cryptographic techniques as a method of encryption can increase system security files are confidential, data security techniques can make use of the RSA algorithm the algorithm which makes use of two keys on the encoding process and its return to the pure message back. By making use of the RSA algorithm as the algorithm to encode the data, then the algorithm can be applied with designing a software using the java programming language. This research aims to be able to design a device that makes use of the RSA algorithm toughness as the encoding algorithm for data and can be installed by building devices that use the java programming language so that it can help the user in securing confidential data before performing the process of storage on storage media. With the creation of this device, is expected to help the user in securing confidential data, and can understand the concept of the RSA algorithm.